256 Implementing and Reinforcing Positive Change to Regional Hand Trauma Service with Introduction of the Golden Patient Initiative. (28th February 2022) - Jayasuriya, N.; Milto, K.; Liew, M.Y.; Douglas, H.; Hughes, D.; Rust, P.
Abstract: Introduction: Significant theatre delays were identified in hand trauma lists at our regional adult hand surgery unity. We aimed to improve theatre delays by implementing a golden patient initiative. Method: Literature review identified the golden patient initiative, which ensures first patient on the list is identified, communicated to multidisciplinary team, and is optimized for theatre. Multi-stage intervention according to change management models (ADKAR and McKinsey 7s) was used. This included (1) a new protocol, (2) educational intervention, 3) poster and (4) a variety of information dissemination methods. To ensure multidisciplinary staff engagement and reinforce positive change, we used multiple verbal, visual and written prompts: trauma co-ordinator-led daily reminders, senior involvement, new column in handover list, verbal reminders at departmental meetings, posters in key areas and widely-accessible reference booklet. Prospective analysis of theatre utilisation pre- and post-intervention to measure impact of intervention. Results: Analysis of emergency general list (EG) and local anaesthetic list (LA) start times identified an average 40 and 20-minute-long delays respectively. Following introduction of golden patient there was a reduction in delays by 9 minutes in LA and 5 minutes in EG. The latest start time improvement by 8 minutes in LA and 50 minutes in EG. There was also a reduction in operation delays by 2.8% in LA and 14.3% in EG. The estimated annual cost saved in EG is approximately £45, 200. Conclusions: We believe that implementing sustainable change is a complex and challenging process. Implementing the golden patient initiative resulted in a positive impact on hand trauma services.